Implementasi model pembelajaran ajak temani mandiri untuk menanamkan profil pelajar Pancasila - Bonifatius Sigit Yuniharto; Ana Fitrotun Nisa (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2022)
Tamansiswa's teaching is also building and supporting education reformation in Indonesia. This study aims to describe the MPATM Model implementation to develop Profil Mahasiswa Pancasila (Pancasila college students profile). The subject of the study was 17 students from Grade VI of SDN Sariharjo. This study used qualitative descriptive research methods through observation, interview, and documentation. The implementation of this MPATM learning model is divided into three phases which are the solicitation phase, companion phase, and independent phase. The implementation of MPATM showed that it could support achieving the learning objectives, such as learning attitude perspective, knowledge, and skills. Students understood how to develop following its uniqueness, implementing independent learning, and developing attitudes which show Profil Pelajar Pancasila based on Kurikulum Merdeka.